1994
DOI: 10.1016/s0022-5347(17)35208-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adrenal Metastasis in Renal Cell Carcinoma

Abstract: The factors predisposing to adrenal metastasis in renal cell carcinoma were reviewed in 695 cases. The overall incidence of adrenal metastasis was 4.3%. The risk of adrenal metastasis correlated with tumors that were on the left side, large and replacing the entire kidney, upper pole in location and of advanced T stage. Nevertheless, microscopic and/or contralateral adrenal metastasis was noted in patients with smaller, lower pole or mid renal tumors. Of 30 patients with adrenal metastasis 9 (30%) had clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3
11

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 11 publications
3
52
3
11
Order By: Relevance
“…Notably, previous studies have demonstrated that contralateral adrenal metastases are able to grow to a considerable size, even when originating from only a small number of metastatic RCC cells, and without metastasizing to other organs; therefore, the adrenal gland may have an increased affinity for RCC spread compared with other organs (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous studies have demonstrated that contralateral adrenal metastases are able to grow to a considerable size, even when originating from only a small number of metastatic RCC cells, and without metastasizing to other organs; therefore, the adrenal gland may have an increased affinity for RCC spread compared with other organs (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Perinefritik boşlukta kontrastlanan nodülün mevcudiyeti oldukça spesifik bir bulgu olmakla birlikte sensitivitesi sadece %46 olarak belirtilmiştir (20). İpsilateral adrenal bez tutulumu %4,3 oranında tanımlanmıştır (21). BT incelemesinde normal olarak tanımlanan bir çalışmada negatif öngörü değeri %100 olarak bulunmuştur.…”
Section: Bilgisayarlı Tomografiunclassified
“…En las piezas de nefrectomía radical la glándula ipsilateral se encuentra afectada en el 4,3% de los casos. Como factores predisponentes se consideran: tumores grandes, de estadio avanzado, localizados en polo superior e izquierdos 49 .…”
Section: Metástasis Suprarrenalunclassified
“…Siempre irá acompañada de linfadenectomía retroperitoneal ampliada, por la elevada correlación entre metásta-sis adrenales y adenopatías positivas (30%) 49 . Si la metástasis es bilateral, circunstancia extremadamente rara, las posibilidades de tratamiento son más complicadas.…”
Section: Metástasis Suprarrenalunclassified